2015
DOI: 10.1177/1079063215609935
|View full text |Cite
|
Sign up to set email alerts
|

Toward Identification of the Sexual Killer: A Comparison of Sexual Killers Engaging in Post-Mortem Sexual Interference and Non-Homicide Sexual Aggressors

Abstract: Establishing a model of sexual assault reflecting psychosocial and behavioral characteristics of perpetrators of sexual killing and rape is necessary for development in risk assessment and intervention. Methodological variations in defining sexual killing have amalgamated serial and non-serial offenders and perpetrators with direct and indirect associations between killing and sexual arousal. This study defined sexual killing specifying that killing should be directly linked to sexual arousal, and sampled 48 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 49 publications
4
40
0
Order By: Relevance
“…Recently, Chan and Heide (2016) and Stefanska, Beech, and Carter (2016) published respectively a literature review and a systematic review of the differences and similarities between the two groups of offenders. In the systematic review by Stefanska et al (2016), which examined 10 studies, the authors found some differences between SHOs and NHSOs as to their characteristics: namely, SHOs were more likely to have reported loneliness problems (see Grubin, 1994;Higgs, Carter, & Stefanska, 2015;Marshall, 1989;Milsom, Beech, & Webster, 2003;Nicole & Proulx, 2007;Palermo, 2008) as well as anger issues (see Chene & Cusson, 2007;Grubin, 1994). However, the two groups shared the presence of mental disorders (see Grubin, 1994;Oliver, Beech, Fisher, & Beckett, 2007;Proulx & Sauvêtre, 2007), a criminal history of sexual and violent offense (Grubin, 1994;Nicole & Proulx, 2007;Oliver et al, 2007;Vettor & Beech, 2014), dysfunctional family structure (see Nicole & Proulx, 2007;Oliver et al, 2007), and sexual victimization (Grubin, 1994;Nicole & Proulx, 2007;Oliver et al, 2007).…”
Section: Differences Between Shos and Nhsosmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Chan and Heide (2016) and Stefanska, Beech, and Carter (2016) published respectively a literature review and a systematic review of the differences and similarities between the two groups of offenders. In the systematic review by Stefanska et al (2016), which examined 10 studies, the authors found some differences between SHOs and NHSOs as to their characteristics: namely, SHOs were more likely to have reported loneliness problems (see Grubin, 1994;Higgs, Carter, & Stefanska, 2015;Marshall, 1989;Milsom, Beech, & Webster, 2003;Nicole & Proulx, 2007;Palermo, 2008) as well as anger issues (see Chene & Cusson, 2007;Grubin, 1994). However, the two groups shared the presence of mental disorders (see Grubin, 1994;Oliver, Beech, Fisher, & Beckett, 2007;Proulx & Sauvêtre, 2007), a criminal history of sexual and violent offense (Grubin, 1994;Nicole & Proulx, 2007;Oliver et al, 2007;Vettor & Beech, 2014), dysfunctional family structure (see Nicole & Proulx, 2007;Oliver et al, 2007), and sexual victimization (Grubin, 1994;Nicole & Proulx, 2007;Oliver et al, 2007).…”
Section: Differences Between Shos and Nhsosmentioning
confidence: 99%
“…Findings from these studies were inconclusive as to whether SHOs and NSHOs differed in physical victimization, relationship status at the time of the crime, low self-esteem, and age at the time of crime (Stefanska et al, 2016). As to the crime scene behaviors, the analysis by Stefanska et al (2016) revealed that NHSOs were more likely to have committed vaginal penetration, to plan the crime (see Higgs et al, 2015;Salfati & Taylor, 2006;Vettor & Beech, 2014), and to humiliate the victim (Healey, Lussier, & Beauregard, 2013;Higgs et al, 2015). The findings were inconclusive as to whether the victim was restrained.…”
Section: Differences Between Shos and Nhsosmentioning
confidence: 99%
“…More recently, a systematic review by Stefanska, Beech, and Carter (2016) examined ten published studies comparing the same two groups of offenders. The findings revealed that sexual murderers were less likely to have committed vaginal penetration, to plan the crime (Higgs et al, 2015;Salfati & Taylor, 2006;Vettor & Beech, 2014), and to humiliate the victim (Healey, Lussier, & Beauregard, 2013;Higgs et al, 2015). Moreover, the findings were inconclusive as to whether the victim was restrained as well as if they differed in physical victimization, relationship status at the time of the crime, low self-esteem, and age at the time of crime (Stefanska et al, 2016).…”
Section: Sexual Homicide and Sexual Murderer: A Specific Type Of Crimmentioning
confidence: 99%
“…Interestingly, recent studies have introduced the concept of Post Mortem Sexual Interference Offenders (PMSIOs) (Carter, Mann, & Wakeling, 2008 ;Higgs, Carter, Stefanska, & Glorney, 2017;. This category of offender includes "homicide offenders whose offence contained at least one of the following characteristics, the perpetrator disclosed that he had sexually assaulted the victim after killing them, there was evidence from a pathologist of post mortem sexual behaviour, the perpetrator had disclosed post mortem sexual behaviour, there was evidence of sex with an unconscious or dead victim or the perpetrator disclosed since conviction that they had sexually assaulted the victim after killing them" (Carter and colleagues, 2008 p. 173).…”
Section: Sexual Homicide and Necrophilia: Patterns And Motivationsmentioning
confidence: 99%